Exploring Problem-Based Learning (PBL) and Case-Based Learning (CBL) in Stimulating Cognitive Skills among Medical Students: Analysis of Verbal Interaction - Khoiriyah, Umatul; Wijaya, Diani Puspa (IIUM Medical Journal Malaysia, 2022)
INTRODUCTION: Problem based learning (PBL) has many benefits; however, research on PBL indicates that students are not quite good at integrating knowledge in basic sciences and clinical aspects. Case-based learning (CBL) might be an alternative method to enhance the integration of this knowledge. No research explored the way these two methods stimulate cognitive skills. This study aimed to explore the differences between PBL and CBL in stimulating cognitive skill by analyzing verbal interaction. MATERIALS AND METHODS: This descriptive research was performed at the Faculty of Medicine, Universitas Islam Indonesia (FM UII). Twenty-one undergraduate students contributed voluntarily to this study. The students were then split up randomly into a PBL Group (n=10) and a CBL group (n=11). Each group performed twice discussion meetings facilitated by an experienced tutor. The discussion processes were video recorded and analyzed using a coding scheme categorizing the verbal interaction into five types: cumulative reasoning, exploratory questioning, procedural interaction, handling conflict about knowledge, off-task/ irrelevant interactions. RESULTS: Students in both PBL and CBL groups spent most of their time-sharing cumulative reasoning and then asking exploratory question. Students in the PBL group were more frequently asking exploratory questions. Students in both groups rarely handled conflict about knowledge since it was a high order thinking skill. Students in the CBL group were more frequent than the PBL group in performing procedural interaction. CONCLUSIONS: Students performed various cognitive skills in both PBL and CBL. Each method has its own strengths in stimulating reasoning skills of students.